Successful combination of sequential gene therapy and rescue Allo-HSCT in two children with X-CGD$iImportance of timing - Siler, Ulrich; Paruzynski, Anna; Holtgreve-Grez, Heidi; Kuzmenko, Elena; Koehl, Ulrike; Renner, Eleonore D.; Alhan, Canan; de Loosdrecht, Arjan A. van; Schwäble, Joachim; Pfluger, Thomas; Tchinda, Joelle; Schmugge, Markus; et al. (Current gene therapy, 2015)
We report on a series of sequential events leading to long-term survival and cure of pediatric X-linked chronic granulomatous disease (X-CGD) patients after gamma-retroviral gene therapy (GT) and rescue HSCT. Due to therapyrefractory life-threatening infections requiring hematopoietic stem cell transplantation (HSCT) but absence of HLAidentical donors, we treated 2 boys with X-CGD by GT. Following GT both children completely resolved invasive Aspergillus nidulans infections. However, one child developed dual insertional activation of ecotropic viral integration site 1 (EVI1) and signal transducer and activator of transcription 3 (STAT3) genes, leading to myelodysplastic syndrome (MDS) with monosomy 7. Despite resistance to mismatched allo-HSCT with standard myeloablative conditioning, secondary intensified rescue allo-HSCT resulted in 100 % donor chimerism and disappearance of MDS. The other child did not develop MDS despite expansion of a clone with a single insertion in the myelodysplasia syndrome 1 (MDS1) gene and was cured by early standard allo-HSCT. The slowly developing dominance of clones harboring integrations in MDS1-EVI1 may guide clinical intervention strategies, i.e. early rescue allo-HSCT, prior to malignant transformation. GT was essential for both children to survive and to clear therapy-refractory infections, and future GT with safer lentiviral self-inactivated (SIN) vectors may offer a therapeutic alternative for X-CGD patients suffering from life-threatening infections and lacking HLA-identical HSC donors.
Gesehen am 17.06.2020